Smart tracking technology implementation to reduce inventory loss: A systematic literature review - Edward Rosyidi; Fauzan Budiman; Bintang Wicaksono Adjie; Trinanda Intan Apriyani; Zildjian Ikhya Armeinova; Noviani Putri Sugihartanti (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2027)
Inventory loss is a common issue in inventory management across sectors such as manufacturing, education, and construction. This problem is often caused by limitations of manual recording systems that cannot provide adequate data visibility or real-time asset monitoring. Digital technologies such as Radio Frequency Identification (RFID) and the Internet of Things (IoT) offer solutions to improve inventory management efficiency and reduce the risk of asset loss. This study aims to analyze the implementation of digital technologies in inventory management systems and evaluate their impact on operational efficiency and asset control. The research uses a systematic literature review method by examining relevant national and international journal articles published between 2017 and 2025. The analysis focuses on identifying key findings from previous studies regarding the application of RFID and IoT in inventory tracking systems. The results show that technology-based tracking systems can improve recording accuracy, enable real-time inventory monitoring, and reduce the risk of asset loss. However, several challenges remain, including high initial implementation costs and the readiness of information technology infrastructure.